Կորագիծ ինտեգրալներ - Ապրեսյան, Միքայել
В работе исследованы криволинейные интегралы . Рассмотрены простейшие примеры, которые способствуют углублению знаний учащихся . В математике, при решении задач, возникают разные вопросы , разные трудности . Преодоление возникшей проблемы приводит к решению задач . Важно знать также ход решения типовых задач . Работа содержит решения типовых примеров. The work investigates curvilinear integrals. The elementary examples which promote increasing knowledge of pupils are reviewed. In mathematics, at the solution of tasks, different questions and difficulties arise. Overcoming of the arisen problem leads to the solution of tasks. It is important to know the course of the solution of standard tasks. The work contains solutions of standard examples.
Keywords: Մաթեմատիկայի դասավանդման մեթոդիկա